Validation of Discovery Learning E-Module based on Video Demonstration on Chemical Equilibrium for High School Student - Hardeli Hardeli; Eka Yusmaita; Sri Mulyani; Bundani Sakinah Alora; Purti permatasari (Postgraduate, University of Mataram, 2022)
This study aims to determine the validity of discovery learning-based E-modules integrated with video demonstrations on chemical equilibrium material for high school students. The type of research conducted was research and development (R & D) with the Plomp development model. This study involved six chemistry lecturers at the Faculty of Mathematics and Natural Sciences and the Faculty of Engineering, Padang State University, two high school chemistry teachers from SMAN 7 Padang and MAN 3 Payakumbuh, and involved XI grade students in each school. The data collection technique used was a questionnaire. The research data was processed using Aiken's V formula. Based on the research results, the e-module was in the